THE STUDENTS’ LEARNING INTEREST OF QUIPPER SCHOOL USED BY THE TEACHER IN TEACHING ENGLISH: Descriptive Research - Wahfiuddin Jamil; Andi Tenri Ampa; Ilmiah Ilmiah (Universitas Muhammadiyah Makassar, 2019)
This research aims to investigate the students’ interest in learning English towards the use of Quipper School. In this study, 45-eighth-grade students from three classes at Lab SMP School Unismuh Makassar responded to 20-items of the questionnaire about the use of Quipper School in learning English. The data were then analyzed by means of a descriptive quantitative method followed by the random sampling technique to take the sample. The response of this questionnaire was concluded to answer the research question. The results show that most of the students were interested in Quipper School as a medium of learning English in the class. Some of the most appealing features of Quipper School encompassed self-evaluation, cognitive training, accessibility and updated material. These made them be comfortable with learning English which motivated them to study in order to enhance their English skill. Thus, the use of Quipper School was likely to be an effective medium of instruction, and English Teachers should consider incorporating its use in their classrooms. Eventually, it ensured that they would be prepared to communicate with English as a common language used in the globalization era.